If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2y + -1(2x + -3y) = 0 3x + -2y + (2x * -1 + -3y * -1) = 0 3x + -2y + (-2x + 3y) = 0 Reorder the terms: 3x + -2x + -2y + 3y = 0 Combine like terms: 3x + -2x = 1x 1x + -2y + 3y = 0 Combine like terms: -2y + 3y = 1y 1x + 1y = 0 Solving 1x + 1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 1x + 1y + -1y = 0 + -1y Combine like terms: 1y + -1y = 0 1x + 0 = 0 + -1y 1x = 0 + -1y Remove the zero: 1x = -1y Divide each side by '1'. x = -1y Simplifying x = -1y
| 5(x+3)+2=5(x-8)-3x | | 3x+0-12=0 | | 3x^2+9x=6 | | 5(x-3)+2=5(x-8)-3x | | 54x^4-16x=0 | | -20x+10=-6-12x | | x=-6x^2-8x+10 | | y=-6x^2-8x+10 | | 2/3H-1/H+11=8 | | 8y-3=5y+3 | | 6x^2-2x=28 | | -x^2-6x-15=0 | | (24x-18)(4x+3)= | | 13+2(2x-2)=16-3x-7 | | y+4x=7 | | 4x^2+2x=28 | | 7(2a-b)-5(2b-7a)= | | 10=x+15 | | 2=11-3x | | 4x+1.2=6 | | -5x+2=46 | | X^3+6x^2+6x=0 | | 3/n=15/80 | | -8x+80=8x-80 | | 9b+13=14-2b | | 7y-13=22 | | 9b+13=13-2b | | 600y-240=143 | | (-a-5b+6)2ab= | | x^2-2s-26=0 | | 3x+7=-2x+12 | | 4x-x^7+5x^3= |